2012
DOI: 10.1111/j.1556-4029.2011.02036.x
|View full text |Cite
|
Sign up to set email alerts
|

The Changes of Fourier Transform Infrared Spectrum in Rat Brain*

Abstract: Estimation of the time since death (postmortem interval [PMI]) is one of the most difficult problems in forensic investigations, and many methods currently are utilized to estimate the PMI. The goal of this study was to investigate the changes of attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectra of rat brain from postmortem time 0-144 h. The intensity ratios of major absorbance bands were examined (I(1066)/I(1392), I(1168)/I(1392), I(1234)/I(1454), I(1301)/I(1392), I(1647)/I(2956), I(29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…The ratio between the peak areas of CH 2 symmetric and CH 2 asymmetric stretching was increased by differentiation progression (Figure 5b). In recent years, CH2 symmetric/CH2 asymmetric band was attributed to changes in the cell membrane (39). Our study might reflect a clear change in the membrane of cells in the differentiation procedure.…”
Section: Ftir Spectrum Of Cells In the Differentiation Proceduresmentioning
confidence: 54%
See 1 more Smart Citation
“…The ratio between the peak areas of CH 2 symmetric and CH 2 asymmetric stretching was increased by differentiation progression (Figure 5b). In recent years, CH2 symmetric/CH2 asymmetric band was attributed to changes in the cell membrane (39). Our study might reflect a clear change in the membrane of cells in the differentiation procedure.…”
Section: Ftir Spectrum Of Cells In the Differentiation Proceduresmentioning
confidence: 54%
“…At least three areas of variation were found by comparing the ratios of bands :There are two peaks at about 2850 and 2920 cm -1 , which can be related to the CH 2 symmetric andCH 2 asymmetric stretching vibration bands, respectively (39). The ratio between the peak areas of CH 2 symmetric and CH 2 asymmetric stretching was increased by differentiation progression (Figure 5b).…”
Section: Ftir Spectrum Of Cells In the Differentiation Proceduresmentioning
confidence: 95%
“…"Euthanasia" methods included the "humane" injection of sodium pentobarbital, but also exsanguination and blunt trauma [29,30,31]. In some cases, the type of trauma examined or the actual experiment ended up being the cause of death [32,33,34].…”
Section: Page 6 Of 21mentioning
confidence: 99%
“…Our work is focused on the characterization of postmortem changes in biological tissues with the ATR-FTIR technique in order to determine the time after death. In our previous studies, it has been demonstrated that various absorption intensities or area ratios in an infrared spectrum are strongly correlated with PMI in human and animal tissues including brain, kidney cortex, cardiac muscle and lung [19][20][21][22][23] . However, these studies did not make full use of ATR-FTIR for PMI delimitation because only a few parameters were taken into consideration.…”
Section: Attenuated Total Reflectance-fourier Transform Infrared (Atrmentioning
confidence: 99%